Efficacy and safety of direct oral anticoagulants for preventing venous thromboembolism in hospitalized cancer patients: a national multicenter retrospective cohort study - Wu, Shuyi; Wang, Haiping; Li, Chunbao; Tao, Jingjing; Zhu, Xiaoli; Dai, Hengfen; Duan, Hongfan; Hu, Tian; Li, Miao; Qu, Fenfen; Wei, Yun; Wang, Chunhua; et al. (Frontiers in Pharmacology, 2024)
Introduction Studies on the use of direct oral anticoagulants (DOACs) for preventing venous thromboembolism (VTE) in hospitalized cancer patients are lacking. Therefore, we conducted a multicenter retrospective cohort study to evaluate the efficacy and safety of DOACs versus low-molecular-weight heparin (LMWH) for the primary prevention of VTE in hospitalized cancer patients. Methods Clinical outcomes included thrombosis, VTE, other thrombosis, all bleeding, major bleeding, nonmajor bleeding, and all-cause death. A 1:1 cohort of rivaroxaban and LMWH patients was created by propensity score matching. Results A total of 2,385 cancer patients were included in this study. During the 3-month follow-up period, 129 (5.4%) thrombosis events occurred, 63 (2.7%) of which were VTEs and 66 (2.8%) of which were other thrombosis events. All bleeding occurred in 163 (6.8%) patients, 68 (2.9%) had major bleeding, and 95 (4.0%) had nonmajor bleeding. All-cause deaths occurred in 113 (4.7%) patients. After adjusting for various confounders, the incidence of thrombosis and other thromboses was significantly lower in the rivaroxaban group than in the LMWH group [OR 0.543, 95% CI (0.343–0.859), p = 0.009; OR 0.461, 95% CI (0.241–0.883), p = 0.020]. There were no significant differences in incidence of VTE, total bleeding, major bleeding, nonmajor bleeding, or all-cause death. Conclusion In oncology patients receiving thromboprophylaxis, rivaroxaban has a lower incidence of thrombosis and other thrombosis and a similar incidence of VTE as LMWH and does not increase the risk of bleeding. Rivaroxaban may be an attractive alternative to LMWH for preventing VTE in hospitalized cancer patients.